Insider trading in the European Union and in Brazil: a comparison of the essential elements of its definition - Blachnio-Parzych, Anna; de Castro, Alexander (Journal of financial crime, 2021)
PurposeThe purpose of this study is a comparison of anti-insider trading regulations in the European Union (EU) and in Brazil.Design/methodology/approachThe subject of the comparison are three key elements that define the shape of the protection against insider trading, namely, the definition of inside information, the definition of insiders and the kinds of behaviours that are forbidden.FindingsThere are both differences and similarities between EU and Brazilian legislations on insider trading. The main discrepancies found in the three foci of the analysis seem to relate strongly to the different rationales for the prohibition of insider trading adopted in the two legal systems. In the EU, market egalitarianism and thus the parity of information, are the central concepts, whereas fiduciary duties originally constituted the point of reference in Brazil, although it has been losing importance over time owing to subsequent changes in the legislation. In sum, while anti-insider trading regulations in the EU have a well-defined identity, in Brazil their policy basis seems to be in the process of redefinition.Originality/valueAs of the time of submission of this study no published academic works dedicated substantially to a comparison of the anti-insider trading legislation of the EU and Brazil could be found.